2006
DOI: 10.2146/ajhp050106
|View full text |Cite
|
Sign up to set email alerts
|

National survey of dietary supplement policies in acute care facilities

Abstract: A survey of pharmacy directors in acute care facilities revealed that many had no formal policy regarding dietary supplements and had not implemented planning for such a policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
(16 reference statements)
2
6
0
Order By: Relevance
“…Pharmacy directors have reported concerns about the lack of active ingredient consistency, difficulty in identifying reputable manufacturers, difficulties in identifying DSs, and lack of premarketing safety and efficacy reviews. 17 Similar to previous studies of adult institutions, only 58% of our respondents reported including proof of a DS's quality before adding it the formulary. 17,18 The lack of standards for quality (free of adulterants or contaminants) and variation in the quantity of active ingredients in DSs are major concerns in the United States.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Pharmacy directors have reported concerns about the lack of active ingredient consistency, difficulty in identifying reputable manufacturers, difficulties in identifying DSs, and lack of premarketing safety and efficacy reviews. 17 Similar to previous studies of adult institutions, only 58% of our respondents reported including proof of a DS's quality before adding it the formulary. 17,18 The lack of standards for quality (free of adulterants or contaminants) and variation in the quantity of active ingredients in DSs are major concerns in the United States.…”
Section: Discussionsupporting
confidence: 83%
“…17 Similar to previous studies of adult institutions, only 58% of our respondents reported including proof of a DS's quality before adding it the formulary. 17,18 The lack of standards for quality (free of adulterants or contaminants) and variation in the quantity of active ingredients in DSs are major concerns in the United States. [19][20][21][22][23][24][25][26][27][28][29][30] However, the FDA has just released the final rule on good manufacturing practices for DSs made in the United States that will go into affect in 2008.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Cook et al surveyed the use of complementary medications in hospital practice in Canada and concluded that the use of complementary medications on general medicine wards appeared to be low, whereas the preadmission use of complementary medications appeared common [10]. Based on a US national survey, Bazzie et al [11]. reported that many facilities lacked formal policies on dietary supplement use.…”
Section: Introductionmentioning
confidence: 99%